2021
DOI: 10.1021/acscatal.1c03970
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Catalytic Properties of Isolated Pt2+ Sites in Platinum Phosphide (PtP2)

Abstract: This article describes the synthesis and catalytic properties of supported, 2–3 nm platinum phosphide (PtP2) nanoparticles (NPs). Depending on the P loading, two PtP2 structures are formed, that is, a PtP2 surface on a (metallic) Pt core (Pt@PtP2) and single-phase PtP2 NPs. The structures were determined using extended X-ray absorption fine structure , in situ synchrotron X-ray diffraction, and scanning transmission electron microscopy. In PtP2 NPs, Pt2+ ions are geometrically isolated by P2 2– ions, at a Pt–P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 82 publications
3
25
0
Order By: Relevance
“…High-resolution TEM (HR-TEM) images show lattice fringes with spacings of 0.234, 0.276, 0.228, and 0.282 nm, corresponding to Ru 2 P­(210), Rh 2 P­(200), Pd 5 P 2 (1̅13), and PtP 2 (200), respectively (Figure a–d, insets). These results are in agreement with the XRD patterns and the previously reported values. …”
Section: Resultssupporting
confidence: 93%
“…High-resolution TEM (HR-TEM) images show lattice fringes with spacings of 0.234, 0.276, 0.228, and 0.282 nm, corresponding to Ru 2 P­(210), Rh 2 P­(200), Pd 5 P 2 (1̅13), and PtP 2 (200), respectively (Figure a–d, insets). These results are in agreement with the XRD patterns and the previously reported values. …”
Section: Resultssupporting
confidence: 93%
“…S12†). 33,34 This evidence cooperatively reveals that Pt( ii ) was installed into the UiO-68-SMe crystals by bonding with –SCH 3 groups.…”
Section: Resultsmentioning
confidence: 77%
“…Anderson et al 44 reported that Pd atoms were uniformly isolated on PdP 2 , which led to a higher selectivity in acetylene hydrogenation. Miller et al 45 discovered that no Pt-Pt bond existed in PtP 2 and the isolated Pt sites had similar catalytic properties to single site catalysts.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%